Aluminium oxide nanoparticles induced morphological changes, cytotoxicity and oxidative stress in Chinook salmon (CHSE‐214) cells. Issue 10 (15th April 2015) - Srikanth, Koigoora; Mahajan, Amit; Pereira, Eduarda; Duarte, Armando Costa; Venkateswara Rao, Janapala
Abstract: Aluminium oxide nanoparticles (Al2 O3 NPs) are increasingly used in diverse applications that has raised concern about their safety. Recent studies suggested that Al2 O3 NPs induced oxidative stress may be the cause of toxicity in algae, Ceriodaphnia dubia, Caenorhabditis elegans and Danio rerio . However, there is paucity on the toxicity of Al2 O3 NPs on fish cell lines. The current study was aimed to investigate Al2 O3 NPs induced cytotoxicity, oxidative stress and morphological abnormality of Chinnok salmon cells (CHSE‐214). A dose‐dependent decline in cell viability was observed in CHSE‐214 cells exposed to Al2 O3 NPs. Oxidative stress induced by Al2 O3 NPs in CHSE‐214 cells has resulted in the significant reduction of superoxide dismutase, catalase and glutathione in a dose‐dependent manner. However, a significant increase in glutathione sulfo‐transferase and lipid peroxidation was observed in CHSE‐214 cells exposed to Al2 O3 NPs in a dose‐dependent manner. Significant morphological changes in CHSE‐214 cells were observed when exposed to Al2 O3 NPs at 6, 12 and 24 h. The cells started to detach and appear spherical at 6 h followed by loss of cellular contents resulting in the shrinking of the cells. At 24 h, the cells started to disintegrate and resulted in cell death. Our data demonstrate that Al2 O3 NPs induce cytotoxicity and oxidative stress in a dose‐dependent manner in CHSE‐214 cells. Thus, our current work may serve as a base‐line study for future evaluation of toxicity studies using CHSE‐214 cells. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Chinook salmon (CHSE‐214) cells exposed to aluminium oxide nanoparticles (Al2 O3 NPs) induced dose dependent cytotoxicity. Morphology of CHSE‐214 cells exposed to Al2 O3 NPs were altered at 6, 12 and 24 h of exposure time. Reduction of SOD, CAT and GSH activity followed by an increase in GST and LPO was evident in CHSE‐214 cells exposed to Al2 O3 NPs. Thus our current work may serve as a base line study for future evaluation of toxicity studies using CHSE‐214 cells.